Insomnia During the COVID-19 Outbreak in Brazil - Orsini, Marco Antônio; Stephanie Fernandes do Nascimento, Jacqueline; Azizi, Marco; Cardoso, Carlos Eduardo; Castro, Renata; Santos Moras Nunes, Nicolle; Fernandes do Nascimento, Janie Kelly (Revista de Saúde, 2020)
Introduction: The outbreak of COVID-19 among humans in Brazil and its spread around the world is strongly impacting mental health. Health problems such as anxiety, depression, insomnia and fear were the most related to. High levels of stress during the day can impair quality and time of sleep. Method: The purpose of this article was to update, through a bibliographic search, the effects of the pandemic on sleep disorders, with insomnia being the most related. A systematic search had been carried out in the main databases: Lilacs, Bireme and PubMed. The languages used in the search were Portuguese and English, from articles published this year. Using the following keywords: Sleep quality, COVID-19, Insomnia, Cognitive behavioral therapy. Discussion: The concern about financial and political uncertainties, feelings of impotence and fear of self-contamination and of family members are factors that corroborate with the worsening of the sleep quality of the population and health professionals’ working on the front lines of the fight against the pandemic, leading to increased cases of insomnia. Behavioral Cognitive Therapy, hypnotherapy and social interaction mediated by Web conferencing tools are the best ways to treat these symptoms at the moment. Even so, the brazilian literature on the subject is extremely scarce, making it an extremely relevant subject for future research.